2016
DOI: 10.1071/rd14182
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine improves oocyte and embryo quality in polycystic ovary syndrome patients undergoing intracytoplasmic sperm injection: an alternative to metformin

Abstract: Polycystic ovary syndrome (PCOS) is associated with low-quality oocytes. The aim of the present study was to investigate the effects of metformin (MET), N-acetylcysteine (NAC) and their combination on follicular fluid parameters, oocytes and embryo quality in PCOS patients. A prospective randomised placebo-controlled pilot study on 60 Iranian women with PCOS (aged 25-35 years) undergoing intracytoplasmic sperm injection (ICSI) was designed. Women were divided into four groups (n=15 in each): (1) an MET, admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…Furthermore, it significantly improves seminal fluid volume and viscosity and increase sperm motility in humans [101]. In women suffering from polycystic ovary syndrome, NAC (administered at the doses of 1500 mg/day) has been shown to ameliorate oocyte and embryo quality, representing an alternative to metformin prescription [102]. Such findings support the therapeutic use of this compound for the treatment of human infertility.…”
Section: Antioxidantsmentioning
confidence: 99%
“…Furthermore, it significantly improves seminal fluid volume and viscosity and increase sperm motility in humans [101]. In women suffering from polycystic ovary syndrome, NAC (administered at the doses of 1500 mg/day) has been shown to ameliorate oocyte and embryo quality, representing an alternative to metformin prescription [102]. Such findings support the therapeutic use of this compound for the treatment of human infertility.…”
Section: Antioxidantsmentioning
confidence: 99%
“…Recently, many studies have suggested a central role for oxidative and glycative stresses in the pathogenesis of the PCOS and a decreased antioxidant capacity in patients with PCOS [4][5][6][7]. In addition, it has been demonstrated that PCOS patients consuming antioxidants present an amelioration of ovarian function and morphology, with a reduction of oxidative stress [8].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, mitochondrial augmentation was suggested and recently implemented in humans (Herbert & Turnbull, 2018). In addition, recent studies suggested that antioxidant supplementation, especially with CoQ10, may improve the outcomes of ART cycles with respect to embryo quality and pregnancy outcomes (Cheraghi, Mehranjani, Shariatzadeh, Esfahani, & Ebrahimi, 2016;Luddi et al, 2016;Nashivochnikova, Krupin, & Selivanova, 2015;Safarinejad, 2012).…”
Section: Discussionmentioning
confidence: 99%